Trampoline Drills: Building Air Sense for Dismounts & Landings - Crumley, K. (Technique, 1998)
Trampoline is absolutely essential for developing flipping and twisting. The use of trampoline allows for high skill numbers to be accomplished quickly and without a tremendous amount of body pounding. The focus of this article is strictly the development of air sense, dismounts, and landings. For this reason, it is important to note that there are many fundamentals that I have not taken the time to cover in this brief list of drills. Gymnasts will need to have an understanding of the basic fundamental and preparatory skills before attempting the more advanced drills and sequences. This information is designed for gymnasts that are ready to begin working toward multiple flipping and twisting dismounts. The following drills will not only enhance your gymnast's ability to perform multiple flipping and twisting dismounts, but will also help your gymnasts stick them.